A dialogue of the deaf, or communities of debate? - Štětka, Václav (Teorija in praksa, 2014)
This article presents an analysis of the citizens' engagement with the 2013 Czech Parliamentary Elections campaign on Facebook. While many studies primarily focus on the intensity and forms of adoption of social networks by political actors in campaign communication, we attempt to explore both political parties' use of Facebook as well as the extent and ways of citizen participation on the online election campaign. The empirical base for this study consists of all communication archived over the course of three weeks (before and after the elections) on the Facebook profiles of ten most important Czech political parties. Using quantitative content analysis, we first present an overview of the dynamics and intensity of users' engagement with the campaign, illustrating that some of the small as well as populist parties have managed to mobilize significantly larger part of Facebook population than more established parties. Following that descriptive part, we first turn to the analysis of the actual content of communication, examining primarily the tone of users' comments, and then we move on to a more in-depth, qualitative examination of communication on the profiles of two selected political parties which were very successful in their online mobilization. The results indicate that most party profiles have displayed a rather surprising level of heterogeneity, allowing for dissenting voices to be displayed in what is generally seen as a heavily managed communication environment.
Keywords: Czech Republic; Češka; Družbena omrežja; election; Election campaigns; Elections; Political engagement; Politična angažiranost; Social media; Volilne kampanje; Volitve